2014
DOI: 10.1111/head.12362
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Mind/Body Interventions in Headache: Unanswered Questions and Future Research Directions

Abstract: Background.-Many unanswered questions remain regarding behavioral and mind/body interventions in the treatment of primary headache disorders in adults.Methods.-We reviewed the literature to ascertain the most pressing unanswered research questions regarding behavioral and mind/body interventions for headache.Results.-We identify the most pressing unanswered research questions in this field, describe ideal and practical ways to address these questions, and outline steps needed to facilitate these research effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…2 Migraine accounts for a disproportionate amount of disease burden, particularly among women from the age of 15 to 49. 10 People with migraine are increasingly turning to complementary and integrative health strategies to address migraine, 11,12 particularly when their pharmacologic choices are restricted, such as during pregnancy or due to low efficacy or lack of tolerability of pharmacologic therapies. [3][4][5][6] Behavioral treatments for migraine, including cognitive-behavioral therapies, relaxation, and biofeedback, have demonstrated efficacy to reduce migraine attack frequency and migraine-related disability.…”
Section: Introductionmentioning
confidence: 99%
“…2 Migraine accounts for a disproportionate amount of disease burden, particularly among women from the age of 15 to 49. 10 People with migraine are increasingly turning to complementary and integrative health strategies to address migraine, 11,12 particularly when their pharmacologic choices are restricted, such as during pregnancy or due to low efficacy or lack of tolerability of pharmacologic therapies. [3][4][5][6] Behavioral treatments for migraine, including cognitive-behavioral therapies, relaxation, and biofeedback, have demonstrated efficacy to reduce migraine attack frequency and migraine-related disability.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] The US Headache Consortium's treatment guidelines for prevention of migraines recommends the behavioral interventions of electromyographic biofeedback, relaxation training, thermal biofeedback combined with relaxation training, and cognitive behavioral therapy with Grade A evidence (based on evidence from 39 controlled trials). 12 Approximately half of US adults with migraines report using CAM, especially mind/body therapies such as meditation and yoga. 12 Approximately half of US adults with migraines report using CAM, especially mind/body therapies such as meditation and yoga.…”
mentioning
confidence: 99%
“…People with lower resilience are at risk for greater emotional difficulties such as depression and anxiety, particularly when associated with chronic pain conditions such as migraine. Also, studies on the use of mindfulness and ACT in migraine have demonstrated improvement in patients’ ability to tolerate pain, reduce the use of symptomatic medications and to modulate specific characteristics of the migraine personality (rigidity, low acceptance, and low resilience) . Recently, the calcitonin gene‐related peptide monoclonal antibodies (MAbs), innovative and specific, but costly pharmacological therapies have been introduced and have shown benefit in the management of both episodic and chronic migraine .…”
Section: Monthly Migraine Days and Treatment Doses In Each Treatment mentioning
confidence: 99%